The implication of integrating pediatric education into a pediatric dentistry course for undergraduate dental students - Feng-Chou Cheng; Guay-Fen Huang; Yin-Lin Wang; Hsiao-Hua Chang; Shih-Kai Wang; Ming-Kuang Guo; Chun-Pin Chiang (Journal of Dental Sciences, 2023)
Background/purpose: The separation of dentistry and medicine was initiated as a historical root. The purpose of this study was to evaluate the implication of integrating pediatric education into a pediatric dentistry course (so-called the integrated pediatric dentistry course in this study) for undergraduate dental students through students’ perspectives. Materials and methods: A total of the 34 fifth-year dental students were invited to fill out the questionnaire for the integrated pediatric dentistry course survey after the class of integrated pediatric dentistry course. Results: Of the 34 dental students, all participated in the survey with a 100% valid response rate. The results showed that most of dental students found this integrated pediatric dentistry course to be helpful in improving their knowledge and clinical skills for pediatric dentistry, and knowledge about pediatrics related to dentistry. However, in comparison, the acquisition of clinical skills was less than that of knowledge for pediatric dentistry. Conclusion: We conclude that the integrated pediatric dentistry course improves dental students' knowledge and clinical skills about pediatric dentistry, and knowledge about pediatrics related to dentistry. Considering the effectiveness of this integrated pediatric dentistry course on students’ knowledge and clinical skills, and positive attitude towards pediatric dentistry, this model shows promising for the further use in the dental education.